PENGUKURAN POTENSI ENERGI MATAHARI DAN PERANCANGAN PLTS TERHUBUNG JARINGAN PADA GEDUNG LABORATORIUM TEKNIK 1 ITERA - Harmiansyah; Pramana Putra; Febmartini Evita Nuruli; Fahmi Sapta Hadi; Putri A’isyati Inrum; Rizki Octa Saputra; Muhammad Atma Saputra; Rustam Efendi (Scientific Journal of Mechanical Engineering Kinematika, 2024)
Solar energy is energy that can be continuously renewed and is environmentally friendly. Solar PV design can be done by knowing the potential value of sunlight in an area. Solar panels have a way of converting solar radiation into electrical energy. The aim of this research is to analyze the potential of solar energy, design on-grid based solar modules on the roof of the Engineering Laboratory 1 building and analyze initial investment costs and maintenance of PLTS. This research method was carried out by measuring the amount of solar energy using a solar power meter, designing a grid-connected PLTS system with PVSys software and estimating costs. Based on the research results, it was found that Global Horizontal Irradiance had an average value of 1705.1 W/m2, Direct Radiation of 1662.2 W/m2, Diffuse Radiation of 187.28 W/m2, and Albedo Radiation of 0.10897. The designed PLTS requires a total initial investment value of IDR 699,352,092.-. Annual maintenance and operational costs for the PLTS to be built on the roof of Engineering Laboratory 1 are IDR 6,993,520.92 per year. It is estimated that the life of the solar panels will reach 25 years, so the total maintenance and operational costs will be IDR 174,838,023.-.